Mechanical Properties of Pineapple Braided Fabric Reinforced Epoxy Matrix Composite Fabricated via Vacuum-Assisted Resin Infusion Moulding - C. William, Joshua; S. Ndazi, Bwire; Vollbrecht, Ben (Tanzania Journal of Engineering and Technology, 2025)
Fibres and fabrics obtained from lignocellulosic materials have attracted attention as reinforcements in polymer composites due to their competitive mechanical and ecological benefits. While the potential of randomly oriented pineapple leaves fibres (PALF) in composites have explored in previous studies, the mechanical behaviour of braided PALF fabric composites fabricated via vacuum- assisted resin infusion moulding (VARIM) remains relatively unexplored. In this study the tensile, compression and flexural strengths of epoxy-based composite containing 40 vol.% braided pineapple fabrics, fabricated using VARIM, for load carrying applications were investigated. The results revealed that the three- layered unbleached pineapple braided fabric composites exhibited a tensile strength of 845.1 MPa, the ones from bleached fabrics exhibited a higher tensile strength of up to 996.7 MPa, attributed to enhanced fibre-matrix adhesion resulting from the bleaching process. Additionally, the bleached fabric composites displayed a superior flexural strength of 55.6 MPa for the three-layered configurations, highlighting further the potential of both the bleaching and braiding processes for higher load carrying capacity applications. The results underline the potential of the layered braided pineapple fabric composites, especially the bleached variants, for engineering applications that demand a balance of strength, stiffness, and flexibility. This study not only advances the understanding of the braided PALF fabric composites but also highlights their viability as sustainable alternatives to synthetic fibre reinforcements. By exploiting the properties of pineapple fibre bundles and the VARIM fabrication technique, this research contributes to the endeavours to develop high-performance and eco-friendly composite materials for a diverse engineering application.